Educational intervention on the phytotherapy use for insomnia in older adults - Maigret Calderón Cruz; Lieter Ailed Vidal Rodríguez; Aned Hernández Clavijo; Julio Michel Arias Manganelly; Olenis Alicia Aldana Ramos (Medisur)
Foundation: Insomnia is one of the most common sleep disorders in older adults in today's society. The use of medicinal plants as an alternative treatment has re-emerged worldwide. Objective: to describe the results of an educational intervention on the use of phytotherapy for insomnia in older adults. Methods: intervention study that included 60 older adult patients belonging to Medical Office 13, in Nuevitas, Camagüey, from January 2022 to June 2023. A survey was applied to measure the level of knowledge before and after the educational intervention. The variables age, sex, knowledge about phytotherapy for insomnia, and level of knowledge about medicinal plants to relieve insomnia were analyzed. Results: women predominated, as did older adults between 71 and 80 years of age. At the beginning of the study, they showed low knowledge about the use of phytotherapy for insomnia and after the intervention, an increase in knowledge was observed. Conclusions: a significant increase in knowledge about the use of phytotherapy in insomnia was achieved, which implies a benefit for the elderly by preventing adverse reactions to polypharmacy that, far from preventing insomnia, intensify it.